Plaster with large drug loading capacity and strong permeability and preparation method thereof

A transdermal patch with modified gelatin and nano-silica enhances drug loading and penetration, addressing low drug capacity and absorption issues in traditional ointments, achieving up to 200% improved transdermal efficiency and stability.

CN120305226APending Publication Date: 2025-07-15HENAN TIANZHONGTANG BIOTECHNOLOGY CO LTD

Patent Information

Application Number
CN202510544030.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-28
Publication Date
2025-07-15

AI Technical Summary

Technical Problem

Traditional paste patches have low drug loading, poor drug release efficiency and insufficient transdermal absorption effect. In particular, hot melt glue matrix causes only the surface release of the drug, the hydrogel matrix has limited drug loading, and heavy metal residue problems are difficult to promote.

Method used

The paste matrix composed of modified gelatin, sodium polyacrylate, carbomer 940 and volatile oil complex is adopted to improve the drug loading and permeability through the transdermal penetration peptide of modified gelatin. The grid structure of sodium polyacrylate is combined with the water-locking effect of carbomer 940, and combined with the volatile oil complex and laurazone to open the lipid barrier of the stratum corneum and enhance the cell fluidity.

Benefits of technology

The drug loading volume reaches more than 80%, the transdermal efficiency is increased to 200% of the traditional patch, and the drug stability is ensured through low-temperature mixing process, which significantly improves the transdermal rate and stability of the drug.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_7
    Figure SMS_7
Patent Text Reader

Abstract

The invention relates to a plaster with large drug loading capacity and strong permeability and a preparation method thereof, belongs to the technical field of pharmaceutical preparations, and solves the problems of low drug loading capacity and poor drug transdermal efficiency of the traditional plaster. The plaster comprises the following components in parts by weight: 10-20 parts of gelatin, 5-15 parts of sodium polyacrylate, 1-3 parts of carbomer 9401 and 150-260 parts of glycerol. 0.1 to 0.5 part of a volatile oil compound and 0.2 to 0.4 part of azone; 5 to 15 parts of silicon dioxide, 0.1 to 0.5 part of ethylparaben and 3 to 5 parts of deionized water. The plaster provided by the invention is high in drug loading capacity, the drug loading capacity reaches 80% or above, the permeability is strong, and the preparation process of the plaster is stable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of pharmaceutical preparations, and particularly relates to a plaster with a large drug loading capacity and strong permeability and a preparation method thereof, which is applicable to the transdermal delivery of traditional Chinese medicines and chemical drugs. Background Art

[0002] Traditional plasters generally have problems such as low drug loading capacity, poor drug release efficiency, and insufficient transdermal absorption effect. For example, in hot melt adhesive matrix plasters, due to high internal cohesion, drugs are only released on the surface, and the internal components cannot be effectively utilized; although hydrogel matrix has good drug release properties, its drug loading capacity is limited, and it is difficult to carry high-concentration drugs; while traditional Dan-type plasters are difficult to promote due to heavy metal residue problems.

[0003] Therefore, there is an urgent need to develop a plaster with high drug loading capacity, high permeability, and stable process. Summary of the Invention

[0004] In view of the above analysis, embodiments of the present invention aim to provide a plaster with a large drug loading capacity and strong permeability and a preparation method thereof to solve the problems of low drug loading capacity and poor drug transdermal efficiency of traditional plasters.

[0005] On the one hand, embodiments of the present invention provide a plaster with a large drug loading capacity and strong permeability, including components: 10 - 20 parts of gelatin, 5 - 15 parts of sodium polyacrylate, 1 - 3 parts of carbomer 940, 150 - 260 parts of glycerol; 0.1 - 0.5 part of volatile oil complex, 0.2 - 0.4 part of laurocapram; 5 - 15 parts of silicon dioxide, 0.1 - 0.5 part of ethylparaben, 3 - 5 parts of deionized water.

[0006] Further, the gelatin is modified gelatin, which has the structure shown in Formula I:

[0007]

[0008] Wherein, P is a transdermal penetration peptide; D is gelatin after carboxymethylation modification.

[0009] Further, it also includes components: 0.5 - 2 parts of hydroxypropyl-β-cyclodextrin, 1 - 3 parts of trehalose.

[0010] Further, the crosslinking degree of the sodium polyacrylate is 0.5% - 1.2%, and the particle size is 50 - 150 μm.

[0011] Further, the silicon dioxide is nano-silicon dioxide, and its surface is hydrophobic.

[0012] Further, the volatile oil is selected from one or more of wintergreen oil, eucalyptus oil, and camphor oil;

[0013] Preferably, the volatile oil is selected from wintergreen oil, eucalyptus oil, and camphor oil, and the ratio of wintergreen oil, eucalyptus oil, and camphor oil is 3:2:1;

[0014] Preferably, the ratio of wintergreen oil, eucalyptus oil, and camphor oil is 1:1:1;

[0015] Preferably, the volatile oil is selected from wintergreen oil and eucalyptus oil, and the ratio of wintergreen oil to eucalyptus oil is 2:1.

[0016] Furthermore, it includes the component poloxamer 407.

[0017] Furthermore, it includes the component ascorbyl palmitate.

[0018] On the one hand, the embodiment of the present invention provides a preparation method of a plaster, and the plaster is the plaster described in any one of the above.

[0019] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0020] The plaster provided by the present invention has a high drug loading capacity. Through the grid structure of sodium polyacrylate and the water-locking effect of carbomer 940, the drug loading capacity reaches more than 80%; it has strong permeability. Through the promoting transdermal penetration effect of modified gelatin and the synergistic effect of the volatile oil complex and laurocapram, it opens the lipid barrier of the stratum corneum and enhances the intercellular fluidity respectively, and the transdermal efficiency is increased to 200% of the traditional patch.

[0021] The preparation process of the plaster provided by the present invention is stable. Low-temperature mixing (≤50°C) avoids drug degradation, and hydroxypropyl-β-cyclodextrin is used to encapsulate the volatile oil to improve stability. Detailed Embodiments

[0023] The following specifically describes the preferred embodiments of the present invention, which are used to explain the principle of the present invention and are not used to limit the scope of the present invention.

[0024] A plaster is an external preparation obtained by mixing medicinal materials and a matrix and then spreading them on a backing material, and is divided into types such as traditional black plasters, rubber plasters, and cataplasms. Although the traditional plaster technology has a long history in the field of traditional Chinese medicine, due to the limitations of materials science and preparation technology, its clinical application faces multiple bottlenecks.

[0025] Limitations of traditional matrices: Although the hot melt adhesive matrix can carry a relatively high drug amount (usually ≤60%), its high internal cohesion causes the drug to be released only on the surface layer, and the internal active ingredients cannot effectively penetrate the skin, resulting in drug waste. Although the hydrogel matrix has better drug release properties, its molecular structure limits its drug loading capacity (usually ≤40%), making it difficult to meet the requirements of high-concentration drugs.

[0026] Low transdermal absorption efficiency: The natural barrier function of the stratum corneum of the skin significantly reduces the drug penetration rate. The traditional penetration enhancers (such as a single laurocapram) have limited synergistic penetration enhancement effects on lipophilic and hydrophilic drugs, resulting in insufficient bioavailability.

[0027] To solve the above problems, the present invention provides a plaster with a large drug loading capacity and strong permeability, comprising components: 10 - 20 parts of gelatin, 5 - 15 parts of sodium polyacrylate, 1 - 3 parts of carbomer 940, 150 - 260 parts of glycerol; 0.1 - 0.5 part of volatile oil complex (including wintergreen oil, eucalyptus oil, camphor oil), 0.2 - 0.4 part of laurocapram; 5 - 15 parts of silicon dioxide, 0.1 - 0.5 part of ethylparaben, 3 - 5 parts of deionized water.

[0028] In a possible implementation manner, it further comprises components: 0.5 - 2 parts of hydroxypropyl-β-cyclodextrin, 1 - 3 parts of trehalose.

[0029] Among them, gelatin serves as a natural polymer skeleton, providing flexibility and biocompatibility. Preferably, the molecular weight is 15 - 30 kDa, and the Bloom strength is 200 - 250 g to balance adhesiveness and ductility;

[0030] In a possible implementation manner, the gelatin is modified, including: reacting gelatin with sodium chloroacetate under alkaline conditions to introduce carboxymethyl (-CH2COOH); coupling a transdermal penetration peptide to the modified gelatin through a linker.

[0031] Furthermore, the modified gelatin has the structure of formula 1:

[0032]

[0033] Among them, P is the transdermal penetration peptide; D is the gelatin after carboxymethylation modification.

[0034] In a possible implementation manner, the transdermal penetration peptide is selected from the peptide shown in CN105491982B, and its amino acid sequence is ACLPGVLGSC.

[0035] Among them, gelatin is a high molecular polypeptide obtained by partial hydrolysis of collagen. Its basic structural unit is a chain structure formed by amino acids connected through peptide bonds, and its molecular structure is H2N─[Gly─X─Y] n ─COOH; among them, X is often Pro, and Y is often Hyp or Pro; preferably, gelatin is commercially available pharmaceutical gelatin. After carboxymethylation treatment of the commercially available gelatin, further modification treatment is carried out.

[0036] Among them, the synthesis method of the modified gelatin includes:

[0037] 1. Synthesize linker-gelatin

[0038] S1:

[0039] To a DMF solution (10 mL) of Fmoc-Gly-Gly-Phe-OH (0.807 g, 1.6088 mmol) and 2,3,5,6-tetrafluorophenol (TFP) (0.406 g, 2.5312 mmol), 1,3-diisopropylcarbodiimide (DIC) (0.458 g, 3.4917 mmol) was added at 25 °C. The reaction mixture was stirred at 25 °C for 2 h. Subsequently, the residue was purified by C18 reverse-phase chromatography column, eluting with a gradient of acetonitrile / water (containing 0.1% trifluoroacetic acid, TFA) (0 - 55%). The purified fraction was concentrated and lyophilized to give C1 (1.080 g, yield 94.69%) as a white solid. LCMS (ESI, m / z): [M+H] + = 651.36.

[0040] S2:

[0041] 4-Methylmorpholine (0.122 g, 1.1173 mmol) was added to a DMF solution (5 mL) of D (0.210 g, 3.82 μmol) and C1 (0.188 g, 303.8090 μmol) at 25 °C. After the mixture was stirred for 2 h, morpholine (0.5 mL) was added and stirring was continued for 1 h. The reaction solution was purified by C18 chromatography column, with the eluent being ACN / H2O (containing 0.1% TFA) (gradient 0 - 50%). The purified fraction was concentrated and lyophilized to give C2 (0.245 g, yield 86.7%) as a white solid. LCMS (ESI, m / z): [M+H] + = 326.35.

[0042] S3:

[0043] DIC (0.517 g, 4.0275 mmol) was added to a DMF solution (10 mL) of 2,3,5,6-tetrafluorophenol (0.694 g, 4.3126 mmol) and 2,2-dimethyl-4-oxo-3,8,11,14,17,20-hexaoxa-5-azatricosane-23-carboxylic acid (0.523 g, 1.3965 mmol) at 25 °C. The mixture was stirred at 25 °C overnight. Subsequently, the reaction solution was purified by C18 column chromatography, with the eluent being ACN / H2O (containing 0.1% TFA) (gradient 0 - 55%). The purified fraction was concentrated and dried by lyophilization to give the target product C3 (0.710 g, yield 93.1%) as a yellow oily liquid. LCMS (ESI, m / z): [M+H]+ ==524.20.

[0044] S4:

[0045] 2 - Chlorotrityl chloride resin (1.68 mmol / g, 1.126 g, 1.22 equivalents) was added to dichloromethane (DCM, 30 mL) and left standing for about 30 minutes. After the resin was filtered, it was washed with DCM (10 mL×3). Subsequently, a DCM solution (10 mL) of Fmoc - Lys(Boc)-OH (0.729 g, 1.4815 mmol) and N,N - diisopropylethylamine (DIPEA, 0.615 g, 4.3826 mmol) was added to the resin under a nitrogen atmosphere at 25 °C. The mixture was stirred for 2.5 hours. The resin was filtered again, washed with DMF (10 mL×3), and a DMF solution (15 mL) of 20% piperidine was added. After the mixture was stirred for 0.5 hour, the resin was filtered and washed with DMF (10 mL×3). Then, a DMF solution (15 mL) of Fmoc - N - amino - PEG1 - acid (0.521 g, 1.4697 mmol), HATU (0.656 g, 1.7290 mmol), and DIPEA (0.557 g, 4.2414 mmol) was added to the resin and stirred for 2.5 hours. After the resin was filtered, it was washed with DMF (10 mL×3) and DCM (10 mL×3). Subsequently, a DCM solution (50 mL) of 20% TFA was added, and the mixture was stirred for 2.5 hours and left standing overnight (25 °C). After the resin was filtered, it was washed with a DCM solution of 20% TFA, and the filtrate was evaporated under reduced pressure. The residue was purified by C18 column chromatography with an eluent of ACN / H2O (containing 0.1% TFA) (gradient 0 - 50%). The purified fraction was concentrated and lyophilized to obtain the target product C4 (0.815 g, yield 89.2%) as a yellow semi - solid. LCMS(ESI, m / z): [M + H] + = 474.86..

[0046] S5:

[0047]

[0048] N-methylmorpholine (NMM, 0.229 g, 2.1852 mmol) was added to a DMF solution (5 mL) of C4 (0.322 g, 505.4530 μmol) and C3 (0.322 g, 569.6433 μmol), and the reaction temperature was 25 °C. The mixture was stirred at 25 °C for 2 h, and then purified by C18 column chromatography with eluent ACN / H2O (containing 0.1% TFA) (gradient 0 - 50%). The purified fraction was concentrated and dried by freeze-drying to obtain the target product C5 (0.431 g, yield 98.8%), which was a white solid. LCMS (ESI, m / z): [M-H] + = 849.72.

[0049] S6:

[0050]

[0051] DCC (0.060 g, 290.8019 μmol) was added to a THF solution (2 mL) of C5 (0.166 g, 187.9551 μmol) and N-hydroxysuccinimide (0.072 g, 595.8563 μmol), and the reaction temperature was 25 °C. The mixture was stirred at 25 °C for 3 h, and then filtered. The filter cake was washed with THF (1 mL). The filtrate was concentrated under reduced pressure to obtain the target product C6 (0.125 g, yield 69.9%), which was a yellow oily liquid. LCMS (ESI, m / z): [M+H] + = 948.62.

[0052] S7:

[0053] N-methylmorpholine (NMM, 0.031 g, 278.8248 μmol) was added to a DMF solution (1 mL) of C2 (0.083 g, 81.0794 μmol) and C6 (0.161 g, 166.8429 μmol), and the reaction temperature was 25 °C. The mixture was stirred at 25 °C for 2 h, and then morpholine (0.25 mL) was added, and stirring was continued for 1 h. The residue was purified by C18 column chromatography with eluent ACN / H2O (containing 0.1% TFA) (gradient 0 - 55%). The filtrate was filtered to obtain the target product C7 (0.125 g, yield 89.1%), which was a white solid. LCMS (ESI, m / z): [M+2H] 2+ = 795.49.

[0054] S8:

[0055]

[0056] N-Succinimidyl 6-maleimidocaproate (0.053 g, 133.1097 μmol) and C7 (0.128 g, 78.9423 μmol) in DMF solution (1 mL) were added with N-methylmorpholine (NMM, 0.056 g, 546.7630 μmol), and the reaction temperature was 25 °C. The mixture was stirred at 25 °C for 2 h, and then purified by C18 column chromatography with the eluent of ACN / H2O (containing 0.1% TFA) (gradient 0 - 48%). After filtration of the filtrate, the target product C8 (0.046 g, yield 36.7%) was obtained as a white solid. LCMS (ESI, m / z): [M + 2H] + = 775.36.

[0057] S9:

[0058] C8 (0.046 g, 37.2460 μmol) was dissolved in dichloromethane (DCM, 1 mL), and a DCM solution (1 mL) of trifluoroacetic acid (TFA, 0.1 mL) was added at 25 °C. The reaction mixture was stirred at 0 °C for 8 h, and then acetonitrile (ACN, 2 mL) was added. The reaction solution was evaporated under reduced pressure at 0 °C, and the residue was purified by Prep-HPLC. The purified fractions were concentrated and treated by freeze-drying, and finally the target product C9 (0.0109 g, yield 34.2%) was obtained as a white solid. LCMS (ESI, m / z): [M + 2H] + = 985.89.

[0059] 2. Description of the method for coupling with polypeptides:

[0060] 1). Take the transdermal penetration peptide, and dissolve the polypeptide in buffer (PBS, pH 7.0 - 8.0); under near-neutral (pH 6.5 - 10) or weakly basic conditions, let it stand at room temperature or 4 °C for reaction for 24 h to form disulfide bonds through oxidation reaction;

[0061] 2). Weigh TCEPHCl (Thermo, 20490), and prepare 10 mM and 20 mM aqueous TCEP solutions with ddH2O. Take the diluted transdermal penetration peptide, add it to the solution at a ratio of 1:1 of TCEP to the transdermal penetration peptide, and react at 32 °C for 2 h in a stirred water bath (120 rpm / min) to open the disulfide bonds formed on the polypeptide, so as to facilitate coupling with Linker-gelatin through the opened disulfide bonds; use an ultrafiltration tube with a cut-off molecular weight of 30 KD to centrifuge (4500 rpm, 20 min, repeat 2 times) to remove the unreacted TCEPHCl, and quantify it by ultraviolet spectrophotometer.

[0062] 3). Weigh the linker - gelatin, add DMA to prepare the linker - gelatin solution. Take the transdermal penetration peptide and add it to the solution at a ratio of 1:1 of linker - gelatin to the transdermal penetration peptide. React in a water bath with stirring (120 rpm / min) at 25 °C for 2 hours;

[0063] 4). Use an ultrafiltration tube with a molecular weight cut - off of 30 KD to ultrafilter the conjugate, remove the uncoupled linker - gelatin, transfer it to the storage buffer (20 mM citrate - citric acid buffer, 8% trehalose, 0.06% Tween - 80, pH 6.5), and quantify it by ultraviolet spectrophotometer.

[0064] The modified gelatin obtained by the above method is used as a polymer backbone, which is not only used to increase the drug - loading capacity but also to improve the transdermal rate of the plaster.

[0065] Among them, sodium polyacrylate is used to construct a three - dimensional network structure to enhance the drug - loading capacity. Its cross - linking degree is controlled at 0.5% - 1.2%, and the particle size range is 50 - 150 μm to ensure uniform dispersion of the drug; Carbopol 940 is used to enhance the water - locking ability through carboxyl cross - linking, complement sodium polyacrylate, and is designed with pH responsiveness (pH 5.5 - 6.5) to adapt to the skin microenvironment.

[0066] Among them, the silica is nano - silica, and its surface is modified to be hydrophobic (contact angle > 120°). As a controlled - release carrier, it loads lipophilic drugs to slow down the release rate; hydroxypropyl - β - cyclodextrin is used to encapsulate the volatile oil complex to improve stability and enhance transdermal efficiency; trehalose is used as a cryoprotectant to avoid loss of drug activity during freeze - drying.

[0067] Among them, the loaded drugs are selected from non - steroidal anti - inflammatory drugs, local anesthetics, hormonal drugs, single - herb extracts, compound Chinese medicines, plant essential oils or compound essential oil formulations.

[0068] In a possible implementation, the compound volatile oil: wintergreen oil, eucalyptus oil, camphor oil are compounded in a ratio of 3:2:1, and act synergistically on different skin layers: wintergreen oil (methyl salicylate): targets the lipid barrier of the stratum corneum and enhances the drug diffusion coefficient; eucalyptus oil (1,8 - cineole): acts on the epidermis layer to promote intercellular fluidity; camphor oil: stimulates the microcirculation of the dermis layer to accelerate drug absorption.

[0069] In a possible implementation, it also includes the component: poloxamer 407, which forms micelles to encapsulate poorly soluble drugs, improves their solubility, prevents the precipitation of drugs during storage or use, and its surfactant properties can slightly change the stratum corneum structure to assist drug penetration without damaging the skin barrier.

[0070] In a possible implementation, it further includes ascorbyl palmitate. When used in combination with laurocapram and volatile oil, it can further improve the solubility and skin permeability of the drug by forming a mixed micelle or microemulsion system.

[0071] Furthermore, the paste components are uniformly coated and formed after processing to obtain the paste.

[0072] On the one hand, the present invention also provides a preparation method of a paste, including:

[0073] S1: Prepare the volatile oil complex;

[0074] S2: Prepare the gel matrix;

[0075] S3: Premix the volatile oil complex, laurocapram, ethylparaben and silica, and then add them to the gel matrix and stir and mix.

[0076] S4: Uniformly coat and form the mixture, dry it and then cut it to obtain the paste.

[0077] In a possible implementation, the preparation method of the paste includes:

[0078] S1: Prepare the volatile oil complex: Mix wintergreen oil, eucalyptus oil and camphor oil in a ratio of 1:1:1, add 10-15wt% hydroxypropyl-β-cyclodextrin, ball mill and then extract with ethanol-polyethylene glycol (volume ratio 10:3), and concentrate to obtain the composite volatile oil;

[0079] S2: Prepare the gel matrix: Mix modified gelatin, sodium polyacrylate, carbomer 940, glycerol and deionized water, and stir at 400r / min until homogeneous;

[0080] S3: Premix the volatile oil complex, laurocapram, ethylparaben and silica, add them to the gel matrix, and stir at a constant temperature of 50°C for 30 minutes;

[0081] S4: Coating and forming: Coat the mixture on the non-woven fabric, dry it at 45°C and then cut it, and seal and package.

[0082] In a possible implementation, S1 includes:

[0083] S101: Mix wintergreen oil, eucalyptus oil and camphor oil in a ratio of 1:1:1 to obtain the volatile oil;

[0084] S102: Prepare the volatile oil microspheres by ultrasonic-spray drying;

[0085] S103: Ball mill and mix diclofenac with nano-silica (rotation speed 300rpm, 2h);

[0086] S2 includes: mixing modified gelatin, sodium polyacrylate, carbomer 940, poloxamer 407, and deionized water, and stirring at 400 r / min until homogeneous;

[0087] S3 includes: premixing volatile oil microspheres, nano-silica, ethylparaben, and laurocapram, adding them to the gel matrix, and mixing at low temperature through a twin-screw extruder;

[0088] S4 includes: mixing at low temperature through a twin-screw extruder and injecting into a microfluidic chip for coating and molding.

[0089] In a possible implementation, S1 includes: after mixing wintergreen oil and eucalyptus oil (wintergreen oil:eucalyptus oil = 2:1), embedding them with hydroxypropyl-β-cyclodextrin (1:1.5) by freeze-drying;

[0090] S3 includes: mixing the volatile oil complex, gel matrix, laurocapram, trehalose, ascorbyl palmitate, and ethylparaben at 40 °C through a planetary mixer (vacuum degree -0.08 MPa) to avoid air bubbles;

[0091] Compared with the prior art, the plaster provided by the present invention has a high drug loading capacity. Through the grid structure of sodium polyacrylate and the water-locking effect of carbomer 940, the drug loading capacity reaches more than 80%; it has strong permeability. Through the transdermal penetration-promoting effect of modified gelatin and the synergistic effect of the volatile oil complex and laurocapram, the lipid barrier of the stratum corneum is opened and the intercellular fluidity is enhanced respectively, and the transdermal efficiency is increased to 200% of the traditional patch.

[0092] The plaster preparation process provided by the present invention is stable. Mixing at low temperature (≤50 °C) avoids drug degradation. Hydroxypropyl-β-cyclodextrin is used to embed the volatile oil, improving stability.

[0093] Example 1

[0094] Composition of the plaster: 15 parts of modified gelatin, 10 parts of sodium polyacrylate, 2 parts of carbomer 940, 200 parts of glycerol, 0.3 parts of volatile oil complex, 0.3 parts of laurocapram, 10 parts of nano-silica, 0.2 parts of ethylparaben, and 4 parts of deionized water.

[0095] Preparation method: including the steps:

[0096] S1: Preparation of the volatile oil complex: Mix wintergreen oil, eucalyptus oil, and camphor oil in a ratio of 1:1:1, add 12 wt% hydroxypropyl-β-cyclodextrin, grind them, extract with ethanol-polyethylene glycol (volume ratio 10:3), and concentrate to obtain the composite volatile oil;

[0097] S2: Preparation of the gel matrix: Mix modified gelatin, sodium polyacrylate, carbomer 940, glycerol, and deionized water, and stir at 400 r / min until homogeneous;

[0098] S3: Premix the volatile oil complex, laurocapram, ethylparaben and silicon dioxide, add them into the gel matrix, and stir at a constant temperature of 50 °C for 30 min;

[0099] S4: Coating and forming: Coat the mixture on the non-woven fabric, dry it at 45 °C and then cut it, and seal and package.

[0100] Among them, the drug loading of the plaster is 82%, and the transdermal rate is 35.6 μg / cm 2 ·h; Stability (impurity content, 6 months, %): 0.28.

[0101] Example 2

[0102] Composition of the plaster: 20 parts of modified gelatin, 15 parts of sodium polyacrylate, 3 parts of carbomer 940, 260 parts of glycerol, 0.5 part of volatile oil complex (wintergreen oil:eucalyptus oil:camphor oil = 1:1:1), 0.4 part of laurocapram, 15 parts of nano-silicon dioxide, 0.5 part of ethylparaben, 5 parts of deionized water.

[0103] The preparation method is the same as that of Example 1.

[0104] Among them, the drug loading of the plaster is 85%, and the transdermal rate is 38.2 μg / cm 2 ·h; Stability (impurity content, 6 months, %): 0.31.

[0105] Example 3

[0106] Composition of the plaster: 18 parts of modified gelatin, 12 parts of sodium polyacrylate, 2.5 parts of carbomer 940, 12 parts of nano-silicon dioxide (loaded with diclofenac), 1.5 parts of hydroxypropyl-β-cyclodextrin (embedded with composite volatile oil), 3 parts of poloxamer 407, 0.35 part of laurocapram, 0.5 part of ethylparaben, 5 parts of deionized water.

[0107] Preparation method:

[0108] S1: Prepare the volatile oil complex;

[0109] S101: Mix wintergreen oil, eucalyptus oil and camphor oil in a ratio of 3:2:1 to obtain the volatile oil;

[0110] S102: Prepare the volatile oil microspheres by ultrasonic-spray drying;

[0111] Among them, by using the ultrasonic-spray drying method, mix the volatile oil with hydroxypropyl-β-cyclodextrin (mass ratio 1:2), ultrasonically treat (40 kHz, 200 W) for 10 min and then spray dry to form microspheres with a particle size ≤5 μm and an encapsulation efficiency ≥95%;

[0112] Among them, the inlet air temperature is 80 °C and the outlet air temperature is 45 °C to avoid degradation of heat-sensitive components.

[0113] S103: Mix diclofenac with nano-silica by ball milling (rotation speed 300 rpm, 2 h);

[0114] S2: Prepare the gel matrix: Mix modified gelatin, sodium polyacrylate, carbomer 940, poloxamer 407, and deionized water, and stir until homogeneous at 400 r / min;

[0115] S3: Premix volatile oil microspheres, nano-silica, ethylparaben, and azone, add them to the gel matrix, and mix at low temperature through a twin-screw extruder;

[0116] S4: Mix at low temperature through a twin-screw extruder, and inject and coat into a microfluidic chip for molding.

[0117] Among them, a twin-screw extruder (temperature ≤ 50 °C) is used, and modified gelatin, sodium polyacrylate, and carbomer 940 are fed in stages, with a shear rate of 100 - 200 s-1 to ensure homogeneity without bubbles;

[0118] Among them, the drug is loaded in two steps - the lipophilic components are premixed in nano-silica, and the water-soluble components are dispersed in the glycerol-water phase, and are precisely mixed through a microfluidic chip (channel diameter 200 μm), and the coating thickness is 0.4 mm.

[0119] Among them, the drug loading amount of the plaster is 88%, and the transdermal rate is 42.3 μg / cm 2 ·h; Stability (impurity content, 6 months, %): 0.30.

[0120] Example 4

[0121] Composition of the plaster: 20 parts of gelatin, 15 parts of sodium polyacrylate, 3 parts of carbomer 940, 260 parts of glycerol, 0.5 part of volatile oil complex (wintergreen: eucalyptus: camphor oil = 1:1:1), 0.4 part of azone, 15 parts of nano-silica, 0.5 part of ethylparaben, and 5 parts of deionized water.

[0122] The preparation method is the same as that of Example 1.

[0123] Among them, the drug loading amount of the plaster is 86%; the transdermal rate is 15.03 μg / cm 2 ·h; Stability (impurity content, 6 months, %): 0.93.

[0124] Example 5

[0125] Composition of the plaster: 12 parts of modified gelatin, 8 parts of sodium polyacrylate, 1.5 parts of carbomer 940, 180 parts of glycerol, 0.2 parts of volatile oil complex (wintergreen oil:eucalyptus oil = 2:1), 0.25 parts of laurocapram, 2 parts of trehalose, 0.5 parts of ascorbyl palmitate, 10 parts of mesoporous silica (loaded with ibuprofen), 0.3 parts of ethylparaben, 4 parts of deionized water.

[0126] Preparation method:

[0127] S1: Preparation of volatile oil complex: After mixing wintergreen oil and eucalyptus oil (wintergreen oil:eucalyptus oil = 2:1), they are embedded with hydroxypropyl-β-cyclodextrin (1:1.5) by freeze-drying method;

[0128] Specifically, raw material preparation: Mix wintergreen oil and eucalyptus oil at 2:1 (v / v) (ultrasonic homogenization for 10 min in advance, 40 kHz); hydroxypropyl-β-cyclodextrin (HP-β-CD); weigh it with volatile oil at a mass ratio of 1:1.5 (HP-β-CD:volatile oil);

[0129] Solution preparation: Dissolve HP-β-CD in ultrapure water to prepare a 10% (w / v) solution (such as 10 g HP-β-CD + 90 mL of water); slowly add the volatile oil complex, and stir magnetically (600 rpm, 25 °C) for 24 hours to form an inclusion suspension; ultrasonically treat the suspension (power 200 W, frequency 40 kHz) for 30 minutes to promote inclusion.

[0130] Freeze-drying parameters: Temperature: -45 °C - 25 °C;

[0131] Vacuum degree: 0.01 - 0.2 mbar;

[0132] Heating rate: Heat up at 0.5 - 1 °C / h.

[0133] S2: Preparation of gel matrix: Mix modified gelatin, sodium polyacrylate, carbomer 940, glycerol, and deionized water, and stir at 400 r / min until homogeneous;

[0134] S3: Mix the volatile oil complex, gel matrix, laurocapram, trehalose, ascorbyl palmitate, and ethylparaben at 40 °C by a planetary mixer (vacuum degree -0.08 MPa) to avoid bubbles;

[0135] Among them, the method for loading ibuprofen on mesoporous silica includes: Dissolve ibuprofen in ethanol, inject it into mesoporous silica (pore diameter 4 nm), and evaporate the solvent under reduced pressure;

[0136] S4: Coating thickness is 0.4 mm, sealed with an aluminum-plastic composite film, and irradiated and sterilized (dose 10 kGy);

[0137] Among them, the drug loading of the plaster is 98.5%, and the transdermal rate is 32.1 μg / cm 2 ·h; Stability (impurity content, 6 months, %): 0.35.

[0138] Example 6

[0139] The difference from Example 1 is that sodium polyacrylate and Carbomer 940 are not added.

[0140] Among them, the drug loading of the plaster is 40%, and the transdermal rate is 12.1 μg / cm 2 ·h; Stability (impurity content, 6 months, %): 2.75.

[0141] Comparative Example 1:

[0142] Commercially available hydrogel patch: Loxoprofen Sodium Patch.

[0143] Among them, the drug loading of the plaster is 38%, and the transdermal rate is 18.4 μg / cm 2 ·h; Stability (impurity content, 6 months, %): 1.8.

[0144] Performance test methods and conditions:

[0145] 1. Drug loading detection:

[0146] Detection method: High performance liquid chromatography (HPLC)

[0147] Detection instrument and conditions: Agilent 1260 Infinity II HPLC, C18 chromatographic column (4.6×250 mm, 5 μm); Acetonitrile - phosphate buffer solution (pH 3.0, 50:50 v / v), flow rate 1.0 mL / min; Detection wavelength is set according to the maximum absorption peak of the drug, such as for diclofenac λ = 276 nm;

[0148] Sample treatment: Accurately weigh the plaster sample (about 0.1 g), dissolve it in 10 mL of methanol, and ultrasonically extract for 30 min; Centrifuge (10,000 rpm, 10 min), take the supernatant and filter it through a 0.22 μm filter membrane;

[0149] Standard curve: Prepare drug standard solution with 5 concentration gradients, linear range 1 - 100 μg / mL (R 2 > 0.999);

[0150] Calculation formula: Drug loading (%) = (theoretical dosage / measured drug amount) × 100%

[0151] 2. Transdermal rate detection

[0152] Detection method: Franz diffusion cell method (in vitro transdermal experiment)

[0153] Detection conditions:

[0154] Skin model: Ex vivo porcine skin (thickness 0.5 - 0.8 mm), fixed in a diffusion cell after pretreatment. Among them, the ex vivo porcine skin needs to remove subcutaneous fat, be stored at -20 °C and thawed before use;

[0155] Receiving solution: pH 7.4 phosphate buffer (containing 0.5% SDS), volume 8 mL, magnetic stirring (300 rpm);

[0156] Temperature: 32 ± 0.5 °C (simulating the human skin surface temperature);

[0157] Sampling time points: 1, 2, 4, 8, 12, 24 hours;

[0158] Drug quantification: HPLC is used to detect the drug amount in the receiving solution;

[0159] Calculation formula:

[0160] Steady - state transdermal flux (Jss): J ss = Q / (A × t) (μg / cm 2 ·h)

[0161] Wherein, Q - cumulative transdermal amount, A - diffusion area, t - time;

[0162] 3. Stability detection

[0163] Detection method: Accelerated stability test

[0164] Detection conditions: Accelerated test: 40 °C ± 2 °C, relative humidity 75% ± 5%, stored for 6 months (equivalent to 25 °C / 60% RH, 24 months);

[0165] Detection index: Impurity content: HPLC is used to detect degradation products and calculate the total impurity percentage;

[0166] Instrument and chromatographic conditions: High - performance liquid chromatograph (HPLC); Chromatographic column: C18 reversed - phase chromatographic column (4.6 × 250 mm, 5 μm); Mobile phase: Phase A: 0.05 M potassium dihydrogen phosphate buffer (pH 3.0, adjusted with phosphoric acid); Phase B: acetonitrile;

[0167] Sample treatment: Accurately weigh the plaster sample (about 0.1 g), cut it into pieces and add 10 mL of methanol - water (70:30 v / v) mixed solvent; Ultrasonic extraction for 30 min (power 200 W, frequency 40 kHz); Centrifuge (10,000 rpm, 10 min), take the supernatant and filter it through a 0.22 μm filter membrane.

[0168] Sample analysis: Inject the blank solution, standard solution, and sample solution successively; record the chromatogram and mark the main peak and each impurity peak.

[0169] Calculation formula: Total impurities (%) = (∑Areas of each impurity peak × Response factor) / (Area of the main peak × Response factor of the main component + ∑Areas of each impurity peak × Response factor) × 100%

[0170] Among them, response factor: If the standard product of the degradation product is not available, the default response factor = 1 (assuming the same response as the main component).

[0171] Safety test:

[0172] 1. Skin irritation test

[0173] Test method:

[0174] Experimental model: New Zealand white rabbits (6 rabbits per group), depilate the back skin (4 cm 2 ); Treatment group: Apply a closed patch containing the paste (0.5 g / cm 2 ); Control group: Apply the blank matrix patch; Exposure time: Apply continuously for 24 hours, and observe for 24, 48, and 72 hours after removal; Scoring criteria: Evaluate erythema and edema according to the Draize scoring system (0 - 4 points).

[0175] Test results:

[0176]

[0177] Conclusion: Non-irritating (total score ≤ 0.5).

[0178] 2. Skin sensitization test (Buehler test)

[0179] Test method: Experimental model: Guinea pigs (10 guinea pigs per group); Sensitization stage: Intradermal injection of 0.1 mL of the paste extract (1% w / v) for 3 consecutive weeks; Challenge stage: On the 28th day, apply the paste (0.2 g / cm 2 ), and observe for 48 hours; The positive control is DNCB (dinitrochlorobenzene); Scoring criteria: Grade according to Magnusson-Kligman (0 - 3 points).

[0180] Test results:

[0181] Group Incidence of allergic reaction Average score Patch group (Examples 1 - 5, 10 in each group) 0%(0 / 10) 0.0 Positive control group (DNCB) 100%(10 / 10) 2.9±0.3

[0182] Conclusion: Non-sensitizing.

[0183] 3. Cytotoxicity test (MTT method)

[0184] Test method: Cell line: Human immortalized epidermal cells (HaCaT); Sample treatment: Plaster extract (1 cm 2 / mL culture medium, extracted at 37°C for 24 hours); Exposure time: Cells were co-cultured with the extract for 24 hours; Detection: MTT method was used to determine cell viability (λ = 570 nm).

[0185] Test results:

[0186]

[0187] Conclusion: Cell viability > 90%, meeting the requirements of ISO 10993-5 (no cytotoxicity).

[0188] 4. Acute percutaneous toxicity test

[0189] Test method:

[0190] Experimental model: SD rats (5 rats per group), plaster was applied (2 g / kg body weight); Observation period: 14 days, body weight, behavior and mortality were recorded; Pathological analysis: Heart, liver, kidney and lung tissues were examined after dissection.

[0191] Test results:

[0192] Index Patch group (Examples 1 - 5) Blank control group Mortality rate 0% 0% Weight change (g) +4.2±2.3 +4.2±1.3 Organ pathological abnormality None None

[0193] Conclusion: No acute toxicity reaction.

[0194] 5. Long-term use safety (sub-chronic toxicity)

[0195] Test method: Experimental model: Rats (10 rats per group), plaster was applied daily (1 g / kg body weight) for 90 days; Detection indicators: Blood biochemistry (ALT, AST, creatinine), histopathology.

[0196] Test results:

[0197]

[0198]

[0199] Conclusion: Long-term use did not significantly affect liver and kidney functions.

[0200] 6. Phototoxicity test (3T3 NRU phototoxicity test)

[0201] Test method: Cell line: Mouse fibroblasts (3T3); Treatment: Plaster extract was co-incubated with cells for 1 hour, followed by UVA irradiation (1.7 J / cm 2 ); Detection: Phototoxicity potential (Photo-Irritation Factor, PIF) was calculated by the neutral red uptake method.

[0202] Test results:

[0203] Group PIF value Conclusion Patch group (Examples 1 - 5) 1.4±0.3 No phototoxicity (PIF < 2) Positive control (chlorpromazine) 15.6 Phototoxicity

[0204] Conclusion: No phototoxicity risk.

[0205] In summary, the plaster of the present invention meets international standards (OECD, ISO, ICH) in terms of skin irritation, allergy, cytotoxicity, acute / long-term toxicity and phototoxicity, and the data show that it has excellent safety; and the plaster of the present invention has a drug loading of more than 80%, a transdermal rate increased by 200%, and significantly better stability than traditional plasters.

[0206] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A plaster with a large drug loading capacity and strong permeability, characterized in that It comprises the following components: 10 - 20 parts of gelatin, 5 - 15 parts of sodium polyacrylate, 1 - 3 parts of carbomer 940, 150 - 260 parts of glycerol; 0.1 - 0.5 part of volatile oil complex, 0.2 - 0.4 part of laurocapram; 5 - 15 parts of silicon dioxide, 0.1 - 0.5 part of ethylparaben, 3 - 5 parts of deionized water.

2. The plaster according to claim 1, wherein: The gelatin is modified gelatin, which has the structure shown in Formula I: Wherein, P is a transdermal penetration peptide; D is gelatin after carboxymethylation modification.

3. The plaster according to claim 1 or 2, characterized in that, It further comprises the following components: 0.5 - 2 parts of hydroxypropyl-β-cyclodextrin, 1 - 3 parts of trehalose.

4. The plaster according to claim 1, characterized in that: The crosslinking degree of the sodium polyacrylate is 0.5% - 1.2%, and the particle size is 50 - 150 μm.

5. The plaster according to claim 1, characterized in that: The silicon dioxide is nano-silicon dioxide, and its surface is hydrophobic.

6. The plaster according to claim 1, wherein: The volatile oil is selected from one or more of wintergreen oil, eucalyptus oil, and camphor oil; Preferably, the volatile oil is selected from wintergreen oil, eucalyptus oil, and camphor oil, and the ratio of wintergreen oil, eucalyptus oil, and camphor oil is 3:2:1; Preferably, the ratio of wintergreen oil, eucalyptus oil, and camphor oil is 1:1:1; Preferably, the volatile oil is selected from wintergreen oil and eucalyptus oil, and the ratio of wintergreen oil and eucalyptus oil is 2:

1.

7. The plaster according to claim 1, characterized in that: It comprises the component poloxamer 407.

8. The plaster according to claim 1, characterized in that: It comprises the component ascorbyl palmitate.

9. A preparation method of a plaster, characterized in that: The plaster is the plaster according to any one of claims 1 - 8.

Citation Information

Patent Citations

  • Peptides for enhancing transdermal delivery

    CN105491982B

Cited By

  • Biodegradable antibacterial medical adhesive as well as preparation method and application thereof

    CN121102558A